Characterization of waxes and residual oil recovered from sunflower oil winterization waste - Chalapud Narvaez, Mayra Carolina (2016)
Two filter cakes from the sunflower oil winterization process were used to recover, fractionate and characterize their oil and wax fractions. Both samples presented high lipid content (75.35 and 58.21% dry basis) composed of 88.1 and 89.1% oil and 11.9 and 8.9% waxes. Recovered oils had a very low free fatty acid content, differences in the degree of deterioration consistent with their fatty acid composition, and significant differences in their wax contents, which were in the order of crude sunflower oils (1356-604 mg/kg). Purified waxes were between 40 and 60 carbon atoms with a fatty alcohol and fatty acid distribution in the range of 18-34 and 14-34 carbon atoms, respectively. Significant differences were found between samples in their wax and fatty acid profiles according to differences between the hybrids studied. DSC thermograms presented differences in the onset temperature (71.98 °C and 75.15 °C), melting peak (76.70 and 80.53 °C) and melting enthalpies (202.77 J/g and 204.35 J/g), with the lower values being exhibited by the sample with higher fatty acid unsaturation and lower content of waxes with more carbon atoms.